Sex-biased parasitism in vector-borne disease: Vector preference? - Cozzarolo, Camille-Sophie (PLoS One, 2019)
Sex-biased infections are a recurrent observation in vertebrates. In many species, males are more parasitized than females. Two potentially complementary mechanisms are often suggested to explain this pattern: sexual differences in susceptibility mainly caused by the effect of sex hormones on immunity and differential exposure to parasites. Exposure is mostly a consequence of host behavioural traits, but vector-borne parasitic infections involve another degree of complexity due to the active role of vectors in transmission. Blood-sucking insects may make choices based on cues produced by hosts. Regarding malaria, several studies highlighted a male-biased infection by Plasmodium sp in great tits (Parus major). We hypothesize that the mosquito vector, Culex pipiens, might at least partially cause this bias by being more attracted to male birds. Intrinsic variation associated to bird sex would explain a preference of mosquitoes for males. To test this hypothesis, we provide uninfected mosquitoes with a choice between uninfected male and female nestlings. Mosquito choice is assessed by sex typing of the ingested blood. We did not observe any preference for a given sex. This result does not support our prediction of a preference of mosquitoes for male great tits during the nestling period. In conclusion, mosquitoes do not seem to have an intrinsic preference for male nestlings. However, sexually divergent traits (e.g. behaviour, odour, metabolic rate) present in adults may play a role in the attraction of mosquitoes and should be investigated.